2018
DOI: 10.1002/ajpa.23442
|View full text |Cite
|
Sign up to set email alerts
|

Mississippian subadults from the Middle Cumberland and Eastern regions of Tennessee: Biological indicators of population interaction

Abstract: These findings suggest that despite cultural differences between the ETR and MCR, there was no large-scale intrusion from an outside population into the ETR during the Late Mississippian Period, or if one occurred, it is biologically invisible. Combined with climatic and archaeobotanical data, results suggest the MCR subadults were under increased stress in their earlier years. This may have been associated with increased interpersonal violence and dependence on few food sources occurring with greater scarcity. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Most scholars have focused on defining the beginning of the Vacant Quarter, or the point at which the MCR was completely abandoned, but we have shown that movements out of the MCR may have begun up to 175 years before the total abandonment of this region, as populations slowly immigrated into neighboring regions. This scenario is compatible with that proposed by Kelso (2013, 2018), based on biological data from Middle Cumberland and Eastern Tennessee Mississippian populations that are incompatible with large-scale migrations in a short period of time.
Figure 5.Proposed timing of migrations from the American Bottom to the Middle Cumberland Region, to the Ridge and Valley between around AD 1200 and 1325.
…”
Section: Cultural Change and Coalescencesupporting
confidence: 91%
See 1 more Smart Citation
“…Most scholars have focused on defining the beginning of the Vacant Quarter, or the point at which the MCR was completely abandoned, but we have shown that movements out of the MCR may have begun up to 175 years before the total abandonment of this region, as populations slowly immigrated into neighboring regions. This scenario is compatible with that proposed by Kelso (2013, 2018), based on biological data from Middle Cumberland and Eastern Tennessee Mississippian populations that are incompatible with large-scale migrations in a short period of time.
Figure 5.Proposed timing of migrations from the American Bottom to the Middle Cumberland Region, to the Ridge and Valley between around AD 1200 and 1325.
…”
Section: Cultural Change and Coalescencesupporting
confidence: 91%
“…With the aid of AMS dating, refinements to Mississippian period chronologies have been made in all these regions, most recently in the MCR and Ridge and Valley (e.g., Beahm 2013; Braly 2013; Cobb et al 2023; Dalton-Carriger 2011; Harle 2003; King 2003, 2007; Koerner 2005; Koerner and Dalton-Carriger 2016; Krus and Cobb 2018; Lulewicz 2017, 2018, 2019a, 2019b; Patch et al 2017, 2018; Smith and Moore 2018; Sullivan 2007, 2016, 2018a; Sullivan et al 2022). The improved chronologies have been used in studies of under- or unanalyzed relevant objects made in the homeland as compared with imitations made elsewhere (e.g., Dye 2021; Jones 2018; King 2020; King and Sawyer 2017; Marceaux and Dye 2007; Sharp et al 2020; Smith 2020; Smith and Miller 2009; Smith and Moore 2018), revisits to major sites using modern field techniques including geophysics (Bigman et al 2011; King et al 2011; Lowry et al 2019, 2017; Patch and Lowry 2014; Patch et al 2015, 2016), and bioarchaeological studies (e.g., Harle 2010; Kelso 2013, 2018; McCarthy 2011).…”
mentioning
confidence: 99%
“…The impact of the Little Ice Age would have been profound, prompting demographic shifts and movement across the landscape (Benson et al, 2007, 2009; Meeks & Anderson, 2013). Paleopathological analyses from Late Mississippian MCR sites such as Averbuch reveal that adults and subadults alike were physiologically stressed and suffered malnutrition and infectious disease (Berryman, 1981; D. C. Boyd, 1984; Fojas, 2016; Scopa Kelso, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As I review below, other researchers have applied hazards analysis to estimate demographic changes in survivorship in sites in the Southeast but not the MCR. Work by Worne (2011), Vidoli (2012), and Scopa Kelso (2018), furthermore, have used bioarchaeological approaches to examine human remains from across the MCR during the entire Mississippian period, with research foci on warfare and population movement. Understanding the nuances of population movement and demographic changes within the MCR during the Mississippian period, however, and its relationship with broader cultural phenomena, may be better informed through the study of survivorship.…”
Section: Introductionmentioning
confidence: 99%